Plan de marketing comunicacional para fomento del turismo del cantón Quevedo periodo 2020-2021 - Mejia Vergara, Jean Pierre (2021)
The objective of this research was to develop a tourism communication marketing plan for the Quevedo canton; and in this way contribute to the improvement of the tourist vision that is had of it, and in turn promote the socio-economic development of its inhabitants and the canton in general. It was detected that Quevedo has a high range of tourist attractions and activities to be developed as well as sites that have not yet been promoted as such but that would contribute significantly to tourism. In order to carry out this plan, it has been seen the need to carry out an analysis of the current tourist situation of the canton for which a theoretical investigation of its attractions and most important data was carried out. The research was developed from a descriptive-explanatory modality with observation techniques, taking as a general hypothesis that the communication marketing plan affects the promotion and development of tourism in the Quevedo canton of the Los Ríos province.